Melatonin Alleviates Silica Nanoparticle-Induced Lung Inflammation via Thioredoxin-Interacting Protein Downregulation - Je-Oh Lim; Se-Jin Lee; Woong-Il Kim; So-Won Pak; Jong-Choon Kim; Joong-Sun Kim; Young-Kwon Cho; In-Chul Lee; In-Sik Shin (MDPI AG, 2021)
Silica dioxide nanoparticles (SiONPs) have been increasingly used in various industries; however, this has raised concerns regarding their potential toxicity. SiONPs are also a major component in the Asian sand dust that causes pulmonary diseases among the general public. Melatonin exerts some inhibitory effects against lung inflammation. In this study, we explored the therapeutic properties of melatonin against lung inflammation using an SiONPs-induced lung inflammation murine model and SiONPs-stimulated H292 cells, human airway epithelial cell line, by focusing on the involvement of thioredoxin-interacting protein (TXNIP) in the modulation of the MAPKs/AP-1 axis. We induced an inflammatory response by exposing mouse lungs and the H292 cells to SiONPs and confirmed the anti-inflammatory effect of melatonin. Melatonin inhibited the expression of various inflammatory mediators, including TNF-α, IL-6, and IL-1β, in SiONPs-exposed mice and SiONPs-stimulated H292 cells; this inhibition contributed to a decline in inflammatory cell accumulation in the lung tissues. Furthermore, melatonin treatment decreased the expression of MAPKs and AP-1 by downregulating TXNIP, eventually decreasing the production of SiONPs-induced inflammatory mediators. Overall, these data suggest that melatonin reduces SiONPs-induced lung inflammation by downregulating the TXNIP/MAPKs/AP-1 signalling pathway, thereby supporting the use of melatonin as an effective approach to control SiONPs-induced lung inflammation.